Use of LC-MS for The Quantitative Determination of Advanced Glycation End-Products in Ultra-Processed Malaysian Foods: A Protocol Development Pilot Study - Ong, Catriona Kar Yuen; Lai, Joe Yee; Narayanan, Sreelakshmi Sankara; Mohd Yousof, Nor Syaidatul Akmar; Mohamed Shakrin, Norashareena; Yap, Zheng Yu; Mat Daud, Zulfitri Azuan; Abdul Rahman, Salina; Md Noh, Mohd Fairulnizal; Chan, Sook Wah; Karupaiah, Tilakavati (Malaysian Applied Biology, 2025)
Advanced glycation end-products (AGEs) are formed through non-enzymatic reactions between reducing sugars and proteins, accelerated by high-temperature food processing. Excessive dietary intake of AGEs has been linked to chronic diseases such as diabetes, cardiovascular disorders, and neurodegeneration. An AGE content database is lacking for Malaysian foods, unlike database developments in the United States and China. This pilot study aimed to establish a protocol for AGE quantification using liquid chromatography-mass spectrometry (LC-MS) in selected Malaysian foods. Eleven food samples, categorised by processing level according to the Nova classification, were analysed for two major AGE markers - Nε-carboxymethyllysine (CML) and Nε-carboxyethyllysine (CEL). Results showed significant variation in AGE content between samples, with the highest CEL levels found in deep-fried fish balls and steamed grouper fish, while pan-fried chicken sausages had the highest CML concentration; whereas levels in fresh fruits and minimally processed items like rolled oats were below detection. These findings suggest that food processing methods, particularly dry-heat techniques, significantly influence AGE formation. This developed protocol will be applied to a larger number of Malaysian foods to facilitate the development of an AGE food composition reference database for supporting dietary guidance in chronic disease prevention strategies.